Galice 1980-2022 : urbanisation et diversification économique du territoire - Rubén C. Lois González (Cahiers de Civilisation Espagnole Contemporaine)
The last forty years have meant for Galicia the culmination of a set of profound transformations in its territorial organization and in its economy. In order to know the magnitude of the changes, we start with the characterization of the old agrarian complex, of the dominant peasant society in the region until the 1960s. The crisis of this traditional world, the rural exodus and the growth of the cities. A growth of cities that is part of a logic of generalized urbanization, which privileges densified coastal areas and marginalizes the rural regions of the interior. The dynamics of profound change in the patterns of occupation of the territory are the result of a complete transformation in its economic structure. An intense and belated industrialization process takes place, but above all the service sector grows and the productive base diversifies. The evolution followed by Galicia in the last forty years illustrates the accelerated changes that have occurred throughout Spain after the beginning of the democratic period.